Shakespeare in Quebec : Nation, Gender, and Adaptation - Drouin, Jennifer, 1976- (Book collections on Project MUSE., 2014)
In Shakespeare in Qu ebec, Jennifer Drouin analyses representations of nation and gender in Shakespearean adaptations written in Quebec since the Quiet Revolution.